An Overview of Bioactive 1,3-Oxazole-Containing Alkaloids from Marine Organisms - Jinyun Chen; Sunyan Lv; Jia Liu; Yanlei Yu; Hong Wang; Huawei Zhang (MDPI AG, 2021)
1,3-Oxazole chemicals are a unique class of five-membered monocyclic heteroarenes, containing a nitrogen atom and an oxygen. These alkaloids have attracted extensive attention from medicinal chemists and pharmacologists owing to their diverse arrays of chemical structures and biological activities, and a series of 1,3-oxazole derivatives has been developed into therapeutic agents (e.g., almoxatone, befloxatone, cabotegravir, delpazolid, fenpipalone, haloxazolam, inavolisib). A growing amount of evidence indicates that marine organisms are one of important sources of 1,3-oxazole-containing alkaloids. To improve our knowledge regarding these marine-derived substances, as many as 285 compounds are summarized in this review, which, for the first time, highlights their sources, structural features and biological properties, as well as their biosynthesis and chemical synthesis. Perspective for the future discovery of new 1,3-oxazole compounds from marine organisms is also provided.